2014
DOI: 10.1063/1.4890329
|View full text |Cite|
|
Sign up to set email alerts
|

Electrically induced insulator to metal transition in epitaxial SmNiO3 thin films

Abstract: We report on the electrically induced insulator to metal transition (IMT) in SmNiO3 thin films grown on (001) LaAlO3 by pulsed laser deposition. The behavior of the resistivity as a function of temperature suggests that the primary transport mechanism in the SmNiO3 insulating state is dominated by Efros-Shklovskii variable range hopping (ES-VRH). Additionally, the magnetic transition in the insulating state of SmNiO3 modifies the characteristics of the ES-VRH transport. Systematic DC and pulsed current-voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Finally, we note that electronically induced switching associated with the MIT has been reported for a number of other materials (not only for VO 2 ), for example, in a family of Mott insulators AM 4 X 8 (A = Ga, Ge; M = V, Nb, Ta; X = S, Se) [137,138], SmNiO 3 [139], -Pb x V 2 O 5 [140], and H-doped NbO 2 [141].…”
Section: Switching Mechanismsupporting
confidence: 60%
“…Finally, we note that electronically induced switching associated with the MIT has been reported for a number of other materials (not only for VO 2 ), for example, in a family of Mott insulators AM 4 X 8 (A = Ga, Ge; M = V, Nb, Ta; X = S, Se) [137,138], SmNiO 3 [139], -Pb x V 2 O 5 [140], and H-doped NbO 2 [141].…”
Section: Switching Mechanismsupporting
confidence: 60%
“…However, SmNiO 3 exhibits a MIT above room temperature. A recent study of SmNiO 3 thin films by Lederman has confirmed this [20]. The fundamental mechanism driving the MIT in SmNiO 3 is induced Joule self-heating.…”
Section: A Nickelates Titanates and Manganitessupporting
confidence: 52%
“…Such performance achieved in SNO epitaxy on the (110) oriented substrate benefits more for the practical thermistor applications at low temperature ranges, compared to the one achieved in other oriented samples [10] . In Figure 2f value (B=-T 2 TCR) that evaluates the performance of the negative TCR thermistor [26] , and it can be seen that the SNO/LAO(110) sample exhibits a better thermistor performance across a broad-temperature range compared to the previous reports for SNO [10,[21][22][23][24][25] .…”
Section: Anisotropies In Correlated Transportations Ofmentioning
confidence: 99%